Reading comprehension precursors: Evidence of the simple view of reading in a transparent orthography - Sánchez-Vincitore, Laura V.; Veras, Cledenin; Mencía-Ripley, Aída; Ruiz-Matuk, Carlos B.; Cubilla-Bonnetier, Daniel (Frontiers in Education, 2022)
The Simple View of Reading proposes that reading comprehension depends on two general processes –language comprehension and word recognition– and that the contribution of these known processes to reading comprehension vary in time. Specifically, the contribution of word recognition decreases, and the contribution of language comprehension increases with student progress. The first purpose of this study was to test the Simple View of Reading in a large sample of Dominican public-school 2nd and 4th-grade students. The second purpose was to identify other psychosocial or ecological variables that intervene in reading comprehension. The model containing word recognition (as measured by words per minute, pseudowords per minute, and fluency) and language comprehension (as measured by listening comprehension) explained 80% of the variance for reading comprehension. A quantile regression showed that the predictive ability of language comprehension increases when considering reading comprehension scores, while the predictive power of word recognition decreases as reading comprehension progresses. However, when splitting the sample into 2nd and 4th grades, the contribution of word recognition towards reading comprehension remained stable between 2nd and 4th grades. This means that, although the dynamism of the simple view of reading components follows the same pattern reported in the literature, the students evaluated here might reach reading automaticity later than expected, and therefore, more attentional resources need to be allocated towards decoding. The study confirmed the value of phonological awareness as a precursor variable, and also found variability in reading comprehension depending on sex, disability, family language, and home literacy.